PEMERIAN KECAKAPAN REPRESENTASI MATEMATIS SISWA SMP DALAM MATERI BANGUN RUANG SISI DATAR - Kirana Qurotal Aini Prawira; Jarnawi Afgani Dahlan; Tia Purniati (Balai Diklat Keagamaan Bandung, 2023)
This research was carried out to expose the potential for mathematical representation of geometric materials. Students in the middle grades were used for this study. Case study methodology is used to conduct this study from a qualitative perspective. A mathematical representation instrument based on a five-item description is utilised to convey the findings of the inquiry. According to the findings, out of the four indications of